Rancang Bangun Website E-Learning Menggunakan Metode User-Centered Design dan Evaluasi Heuristik - Thomas, Nathanael Richie; Santiyasa, I Wayan; Suhartana, I Ketut Gede; Karyawati, Anak Agung Istri Ngurah Eka; Kadyanan, I Gusti Agung Gede Arya; Supriana, I Wayan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 2 (2022): JELIKU Volume 11 No 2, November 2022, 2022)
The practice of using the internet in everyday life makes online learning more flexible than face-to-face learning. The online learning process is implemented through e-learning websites at various universities. The e-learning website used in online learning is still minimal attention in evaluating and does not apply elements of user experience and usability in it. We can find out whether a user is satisfied by testing the e-learning website to get feedback from the user. The research was conducted using a user-centered design (UCD) method which focuses on solving problems experienced by a user. Questionnaires will be distributed to users who need a new way of learning through Google Forms to get information about the actual problems experienced by users. This study found that the LearningKu website satisfies users with an average heuristic evaluation score of 1.04 or a scale of 1 included in the cosmetic problem category, which means that the problem does not need to be fixed unless there is time left in project work.